‘Confused about Predicting whether This Kid is Good or Not’: The Evaluation of Social Attitude Assessment in Primary Schools - Teci Dyan Listya; Sendagire Sinani (Elementary Education Journal, 2022)
Backgrounds: The study analyzed the evaluation of social attitudes in the primary schools in Karanganyar Regency, Indonesia: honesty, discipline, responsibility, and tolerance. Methods: A qualitative descriptive technique with a case study design was employed in this investigation. There were eight recruits made up of both instructors and pupils. Observation and interview were the approaches utilized in this investigation. Data is evaluated through data reduction, presenting of data, and formulation of conclusions. Technical triangulation and source triangulation were evaluation procedures to evaluate the veracity of the data. Results: This study showed evaluations carried out; there were two evaluations for students and an evaluation for parents at Dabin I RA Kartini Elementary School. The obstacles that were complained about by the teachers were mostly about time constraints. Implications: The results of this study can be a reference for authors, teachers, and school principals in evaluating the assessment of social attitudes correctly Novelty: The present study revealed the evaluation of social attitudes assessment in primary school comprehensively.